The Transmission of al-Manar's Reformism to the Malay-Indonesian World: The Cases of al-Imam and al-Munir - Azra, Azyumardi (Studia Islamika, 1999)
This journal not only directly influenced the spread of Islamic reformism through its own articles, but most importantly also stimulated the publication of similar journals printed in the Maiay-Indonesian world. This paper is an early attempt to delineate and discuss in a comprehensive manner the transmission of Islamic reformism to the Maiay-Indonesian world by means of journals: primarly al-Imam in Singapore and al-Munir in Padang, West Sumatra, and other journals that were published in the area.DOI: 10.15408/sdi.v6i3.723